Uji Perlakuan Kompos Daun Jagung (Zea mays) dan Pupuk NPK Phonska Terhadap Tinggi Tanaman dan Hasil Kacang Tanah (Arachis hypogaea L.) - Randy Kriswanto; Mahdalena Mahdalena (Universitas Widya Gama Mahakam, 2019)
Test of Corn Leaves (Zea mays) Compost and NPK Phonska Fertilizer on Plant Height and Peanut Yield (Arachis hypogaea L.). This study aims to determine the effect of giving corn leaf compost fertilizer and NPK phonska fertilizer and its interactions on the growth and yield of peanuts. The study used a Randomized Block Design with a 4x4 experiment with 2 factorial replications 3 times. The first factor is the dose of compost of corn leaf compost consisting of 4 levels, namely: o0 (control), o1 (100 g / plant), o2 (200 g / plant), o3 (300 g / plant). The second factor is the NPK fertilizer dosage consisting of 4 levels, namely: k0 (control), k1 (5 g / plant), k2 (10 g / plant), k3 (15 g / plant). The results showed that the treatment of corn leaf compost did not have a significant effect on plant height at 30.60, and 90 days after planting, pod weight and number of pods. Phonska NPK fertilizer does not have a significant effect on plant height at 30, 60, and 90 days after planting, but it has a significant effect on the number of pods and pod weight. The interaction between the compost dose of corn leaf compost and NPK phonska had no significant effect on plant height, pod weight and number of pods.